Agile Governance: The Urgency of Handling Forest and Land Fires in Riau Province - Adni, Dita Fisdian; Zubaidah, Evi; Baharuddin, Tawakkal (Jurnal Manajemen Pelayanan Publik, 2024)
The research focuses on the serious threat that land or forest fires pose to Riau Province, with their profound effects on the environment, society, and economy. This research aims to identify urgent interests related to fire problems in Riau Province, analyze factors that support and hinder fire management, and develop policy recommendations to improve mitigation efforts. The data analysis process in this research relies on the Nvivo 12 Plus platform, allowing for more efficient collection, presentation and processing of qualitative data. The research results show several factors that support the implementation of agile governance, including active stakeholder involvement, adequate use of technology, and development of an integrated Geographic Information System (GIS). However, inhibiting factors were found, such as lack of resources and resistance to change. The proposed policy recommendations include strengthening stakeholder involvement through collaborative forums, improving technological infrastructure, increasing public awareness, developing rapid response protocols, regular monitoring and evaluation, strengthening laws and law enforcement, and promoting inter-regional and inter-institutional cooperation. The urgency reflects the necessity of responding promptly to prevent the damaging effects of forest and land fires on the environment, public health, and local economy.